Peran Sistem Kearsipan dalam Menunjang Efisiensi Kerja Dinas Perpustakaan dan Kearsipan Kota Padang - Yanti, Fitri; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
Abstract The purpose of this study is to describe the role of the filing system in supporting work efficiency in the Padang City Library and Archives Service. The writing of this paper uses descriptive research methods with data collection techniques through interviews. Based on the results of the study it can be concluded as follows. (1) The filing system applied in the Padang City Library and Archives Service uses a substitution system, this substitution system is carried out in each area of expertise so that employees and archivists are not fixed with a particular field and gain experience with archives. (2) Archival management in the Padang City Library and Archives Service must know the distribution of archives. (3) The contribution of records management in supporting the efficiency and effectiveness of the work of employees in the Padang City Library and Archives Service. The effectiveness in managing records in an office is influenced by employees working in the filing unit.Keywords: system role, filing, work efficiency.